A Randomized, Placebo‐ and Positive‐Controlled, Single‐Dose, Crossover Thorough QT/QTc Study Assessing the Effect of Daprodustat on Cardiac Repolarization in Healthy Subjects. Issue 6 (17th April 2017) - Caltabiano, Stephen; Collins, Jon; Serbest, Gul; Morgan, Lisa; Smith, Deborah A.; Ravindranath, Ramiya; Cobitz, Alexander R.
Abstract: Daprodustat (GSK1278863) is a prolyl hydroxylase inhibitor in phase 3 clinical studies for the treatment of anemia associated with chronic kidney disease. This study was conducted to evaluate the effect of daprodustat on cardiac repolarization and enrolled 55 healthy adult male (29) and female (26) subjects who received single‐dose 75 and 500 mg daprodustat, 400 mg moxifloxacin, and placebo. Mean placebo‐corrected change from baseline QT interval for daprodustat showed no statistically significant increase. However, statistically significant decreases in the ΔΔQTcF were observed for both doses of daprodustat, reaching a lowest value of –2.74 milliseconds for 75 mg and –5.93 milliseconds for 500 mg daprodustat; this minor shortening effect is not considered clinically significant. The moxifloxacin group showed a statistically significant increase in the ΔΔQTcF value, reaching a maximal increase of 11.47 milliseconds at 4 hours. Forty subjects (73%) reported at least 1 adverse event, with the highest incidence with 500 mg daprodustat. This group had a higher incidence of gastrointestinal adverse events compared to the other treatment groups. These results suggest that 500 mg daprodustat was not well tolerated; however, daprodustat at 75 mg was generally well tolerated. No new safety concerns were identified in subjects who received 500 mg daprodustat.